Age‐specific associations between the number of co‐morbidities, all‐cause mortality and public direct medical costs in patients with type 2 diabetes: A retrospective cohort study. Issue 2 (2nd November 2022) - Hong, Sabrina Nan; Mak, Ivy Lynn; Chin, Weng Yee; Yu, Esther Yee Tak; Tse, Emily Tsui Yee; Chen, Julie Yun; Wong, Carlos King Ho; Chao, David Vai Kiong; Tsui, Wendy Wing Sze; Lam, Cindy Lo Kuen; Wan, Eric Yuk Fai
Abstract: Aim: To evaluate the association between the number of co‐morbidities, all‐cause mortality and public health system expenditure in patients with type 2 diabetes (T2D) across different age groups. Materials and Methods: A retrospective observational study of T2D patients using electronic health records in Hong Kong was conducted. Patients were stratified by age (< 50, 50‐64, 65‐79, ≥ 80 years) and the number of co‐morbidities (0, 1, 2, 3, ≥ 4), defined using the Charlson Comorbidity Index and prevalent chronic diseases identified in local surveys. The association between the number of co‐morbidities, all‐cause mortality and direct medical costs was examined using Cox proportional hazard regression and the gamma generalized linear model with log link function. Results: A total of 262 212 T2D patients with a median follow‐up of 10 years were included. Hypertension and dyslipidaemia were the most common co‐morbidities in all age groups. After age stratification, cardiovascular diseases dominated the top pair of co‐morbidities in the older age groups (65‐79 and ≥ 80 years), while inflammatory and liver disease were predominant among younger individuals. Compared with co‐morbidity–free T2D patients, the hazard ratios (95% CI) of death for patients aged younger than 50 and 80 years or older with two co‐morbidities were 1.31 (1.08‐1.59) and 1.25 (1.15‐1.36), respectively, and increased to 3.08 (2.25‐4.21) and 1.98 (1.82‐2.16), respectively, as the number of co‐morbidities increased to four or more. Similar trends were observed for medical costs. Conclusions: Age‐specific co‐morbidity patterns were observed for patients with T2D. A greater number of co‐morbidities was associated with increased mortality and healthcare costs, with stronger relationships observed among younger patients.